Ultra-processed foods consumption among inmates in a women's prison in São Paulo, Brazil - CAF Audi; SM Santiago; MGG Andrade; D Assumpção; PMSB Francisco; AM Segall-Corrêa; R Pérez-Escamilla
ABSTRACT Objectives To assess the consumption of ultra-processed foods among inmates in a women's prison in the State of São Paulo, Brazil. Methods We conducted a cross-sectional study in 2012/2013 with 1,013 female inmates. A structured interview questionnaire was used to collect socio-demographic, self-reported morbidity and healthy lifestyles and health-related behaviors data. The inmates' usual diet was assessed with a food frequency questionnaire. Foods were classified as either natural or minimally processed, processed or ultra-processed. Results Inmates age ranged from 18 to 65 years, 51.7% were black, 80.3% had children, 69.5% smoked, 47% were overweight/obese and half of them had high blood triglycerides. The prevalence of daily consumption of natural or minimally processed foods (rice, beans and cassava flour) was 87.7%. The prevalence of daily consumption of green leafy and other vegetables was 63.7%. Almost two-thirds reported consuming milk and fried chicken frequently. A high prevalence of daily consumption of ultra-processed foods was observed in this study. Hot dog bread and sweet bread with margarine were consumed by 86.5% of the interviewees on a daily basis; sugar sweetened beverages by 68.4%, and biscuits as well as candies by 77.1%. Conclusions The women's diet in the prison is of low quality, and may lead to metabolic alterations, obesity and other comorbidities. It is recommended that the prison's Food Evaluation Committee considers improvements to the quality of the prisoners' diets.